Strategi Dan Harapan Pemuda Dalam Institusi Total - Intan Sari Yuniati; Oki Rahadianto Sutopo (Faculty of Social Science, Universitas Negeri Malang, 2019)
Youth is often constructed as a stage of identity exploration. However, not all young people are able to explore their identity freely. Some young people have to experience transition inside the prison (LPKA). This article explores strategy and hope of the future among youth in prison. This research uses qualitative methods combining observation, in-depth interviews and secondary data to gather relevant data. Despite living inside the prison, they still have hopes about their future. They strategically make plans to convert their on hand stock of capital in order to reach the ideal goal. They also have to convert their capitals effectively in order to negotiate with risk as a form of stigmatization. Reflexive capacity is important to create strategic plans and anticipates unpredictable risk in the future.